Becoming a Perfect Human: Ibn ʽArabī’s Thoughts and Its Spiritual Legacy - Hans Abdiel Harmakaputra (Universitas Islam Negeri Mataram, 2013)
This essay explains the concept of waḥdah al-wujūd, as the central doctrine of Ibn ʽArabī, in its relationship to the concept of perfect human being. As manifestation of God, humans and all creatures ontologically bear the status of hūwa/lā hūwa (He/not He) and inherit God’s names. Therefore, the process to be a perfect human is an effort to cultivate those God’s names in the right manner. Here sharīʽa according to Ibn ʽArabī is irreplaceable in guiding human being unto perfection. In contrast to some antinomian sufis who treated sharīʽa as a set of rules that lost its value when someone has arrived at the stage of mystical union with God, the deepest concern of humanity, Ibn ʽArabī regards sharīʽa as the deepest reality (haqīqa) itself.